CHRONIC FRONTAL SINUSITIS CAUSED BY FUNGAL BALL ASSOCIATED WITH CHRONIC INVASIVE FUNGAL RHINOSINUSITIS: A RARE CASE REPORT AND LITERATURE REVIEW (Vietnam Journal of Community Medicine, 2026)
Background: Fungal rhinosinusitis comprises two main forms: non-invasive and invasive disease. Fungal ball is a common form of non-invasive fungal rhinosinusitis, predominantly affecting the maxillary sinus and rarely occurring as an isolated lesion in the frontal sinus. Chronic invasive fungal rhinosinusitis is a rare entity characterized by a disease course exceeding 12 weeks and typically occurs in patients with mild to moderate immunocompromise. Despite its indolent and often nonspecific clinical presentation, CIFRS may result in bone destruction and extension to the orbit or skull base, leading to severe complications and increased mortality if not diagnosed and treated promptly. Distinguishing between these two forms is therefore crucial for appropriate management and prognostic assessment.Case presentation: We report a rare case of a 71-year-old woman with underlying diabetes mellitus who presented with chronic right frontal headache. Computed tomography of the paranasal sinuses demonstrated complete opacification of the right frontal sinus with central hyperdensities, suggestive of a fungal ball. The patient underwent endoscopic sinus surgery combined with an external frontal sinus approach to achieve complete removal of the lesion. Histopathological examination confirmed an Aspergillus fungal ball. Notably, biopsy of the frontal sinus mucosa revealed tissue invasion by Aspergillus species, establishing the diagnosis of chronic invasive fungal rhinosinusitis.Conclusion: Postoperatively, systemic antifungal therapy was administered, and the patient showed a favorable clinical outcome without neurological or ophthalmic complications.
Keywords: Frontal sinus fungal ball; Invasive fungal rhinosinusitis; Aspergillus; Immunocompromised host; Case report.